Labour training policies in the OAS countries - Rodríguez, Juan Manuel (ILO LimaPE, 2002)
Looks at the economic system, work, on the job training and professional training. Examines changes in professional training institutions and financing professional training. Focuses on youth employment policy and professional training in Latin America.